Empirical planning target volume modeling for high precision MRI guided intracranial radiotherapy. (March 2023) - Stewart, James; Sahgal, Arjun; Zadeh, Mahtab M.; Moazen, Bahareh; Jabehdar Maralani, Pejman; Breen, Stephen; Lau, Angus; Binda, Shawn; Keller, Brian; Husain, Zain; Myrehaug, Sten; Detsky, Jay; et al.
Highlights: An evidence based PTV model for intracranial MR guided radiotherapy was developed. PTV model quantified CTV localization uncertainty across 1329 fractions in 66 patients. A 3 mm PTV margin covered 98% of the CTV in 95% of fractions in 95% of patients. Abstract: Purpose: Magnetic resonance image-guided radiotherapy for intracranial indications is a promising advance; however, uncertainties remain for both target localization after translation-only MR setup and intrafraction motion. This investigation quantified these uncertainties and developed a population-based planning target volume (PTV) model to explore target and organ-at-risk (OAR) volumetric coverage tradeoffs. Methods: Sixty-six patients, 49 with a primary brain tumor and 17 with a post-surgical resection cavity, treated on a 1.5T-based MR-linac across 1329 fractions were included. At each fraction, patients were setup by translation-only fusion of the online T1 MRI to the planning image. Each fusion was independently repeated offline accounting for rotations. The six degree-of-freedom difference between fusions was applied to transform the planning CTV at each fraction (CTVfx ). A PTV model parameterized by volumetric CTVfx coverage, proportion of fractions, and proportion of patients was developed. Intrafraction motion was quantified in a 412 fraction subset as the fusion difference between post- and pre-irradiation T1 MRIs. Results: For the left–right/anterior-posterior/superior-inferior axes, mean ± SD of the rotational fusion differences were 0.1 ± 0.8/0.1 ± 0.8/-0.2 ± 0.9°. Covering 98 % of the CTVfx in 95 % of fractions in 95 % of patients required a 3 mm PTV margin. Margin reduction decreased PTV-OAR overlap; for example, the proportion of optic chiasm overlapped by the PTV was reduced up to 23.5 % by margin reduction from 4 mm to 3 mm. Conclusions: An evidence-based PTV model was developed for brain cancer patients treated on the MR-linac. Informed by this model, we have clinically adopted a 3 mm PTV margin for conventionally fractionated intracranial patients.